Management Implementation of the Bi’ah Lughowiyah Programmes and the Problems in Boarding Based on Madrasah Aliyah - Nabila Nailil Amalia; Himmatul Adzimah; Zakiyah Arifa; Muhammad Ihsan Mahbub (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
The purpose of this study is to describe the management of the implementation of the Bi'ah Lughowiyah program and its problems. The research method used is descriptive qualitative with a case study approach. Research data collected through observation, interviews and documentation. After the data is collected, it is then analyzed by presenting data, data reduction, verification and conclusions. The results of this study: 1) The implementation of the Bi'ah Lughowiyah program applies 3 strategies of Tamtsiliyah, Mumarosah and Ta'bir Syafawi, and the problems in implementing the Bi'ah Lughowiyah program are linguistic problems consisting of a lack of Arabic vocabulary, influenced by mother tongue and lack of expression pattern. While non-linguistic problems are differences in educational background, and the emergence of shame and fear of being wrong. There are efforts to overcome this problem with 3 solutions, namely forming a language driving group, using wall magazines as a medium for learning vocabulary and speech patterns, applying muhadatsah usbu'iyyah with vocabulary that has been written on the bulletin.